Health‐related quality of life and emotional well‐being after epilepsy surgery: A prospective, controlled, long‐term follow‐up. (24th August 2017) - Edelvik, Anna; Taft, Charles; Ekstedt, Gerd; Malmgren, Kristina
Summary: Objective: To evaluate health‐related quality of life (HRQOL) and emotional well‐being in resective epilepsy surgery and nonoperated patients at long‐term follow‐up. Methods: This is a prospective cohort study where patients undergoing presurgical work‐up during 1995–1998 completed the Short‐Form Health Survey (SF‐36) and the Hospital Anxiety and Depression scale (HAD) at baseline, and 2 and 14 years after resective surgery or presurgical evaluation (nonoperated patients). SF‐36 scores were compared to a normative population. Proportions of patients reaching HRQOL changes of minimum clinically important difference (MCID) were calculated. Results: At 14‐year follow‐up, operated patients scored equal to or better than the normative sample on all SF‐36 domains except Social Functioning and Mental Health. Physical component summary (PCS) was better and mental component summary (MCS) was worse than for the normative sample. Nonoperated patients scored worse than the normative sample on five of eight domains, and on PCS and MCS. Change in seizure status from 2 to 14 years did not affect PCS or MCS means. Improvement reaching MCID from baseline to long‐term was seen in 50% (PCS) and 47% (MCS) of operated and in 33% (PCS) and 38% (MCS) of nonoperated patients. Worsening was seen in 18% (PCS) and 22% (MCS) of operated and in 38% (PCS) and 38% (MCS) of nonoperated patients. Differences between groups were nonsignificant. HAD scores did not differ between groups, and the numbers of possible or probable cases were low. Patient satisfaction with surgery was higher in operated seizure‐free patients. Only 5% of all operated patients considered surgery not to be overall beneficial. Significance: At the group level, HRQOL was stable 14 years after surgery compared to after 2 years. Social Functioning and Mental Health were still below, but other domains were similar to the normative sample. Individual patterns did not follow seizure outcome changes, indicating that multiple factors are important for long‐term HRQOL.